Implementasi Pola Sosialisasi Represipatif Di Pesantren Immim Putra Makassar Dalam Pembentukan Karakter Santri Yang Unggul - Mursyid, Mursyid (Universitas Negeri Makassar, 2018)
The purpose of his study is to find out how the pattern of repressivatife applied, how the students respond to the pattern of repressivatife socialization during socializing process, and how the impact caused by the implementation of repressivatife socialization pattern in the process of guiding the students, especially at Pesantren IMMIM Putra Makassar. This is a qualitative research of phenomenology by using qualitative descriptive analysis, a research which is done by getting the illustration of a situation and events or various phenomenon concretely about research object or research problem. Methods in collecting data are done trough library research, field research (observation, interview, and documentation). Data analysis is done by data reduction, data presentation and coclusion or data verification. Repessivatife socialization is a pattern of socialization that combines the pattern with repressive socialization and particivatife socialization in a synergistic socialization process. The results of this study indicate that the way of applying the pattern emphasized on cultivating students understanding of the goals and meanings in each established rule, through the students involvement, whit certain mechanisms and maximizing the structural fungtions as a cooperated team. By having a clear understanding of the pattern, the student can ancourage their positive attitude towards this reprssivatife pattern, wich is marked by the proactive attitude during guiding process. The impact is the establishment of cooperatin between the guider and the students during the process, the growing sense of comfort for students in the cottage, wich then encourages the growth of confidence, creativity, and also showing the habitual acts of superior characters among student at muslim school.